2006
DOI: 10.1080/10790268.2006.11753863
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Pacing in Spinal Cord Injury: Case Report and Clinical Commentary

Abstract: Background/Objective: A significant fraction of patients with cervical spinal cord injury suffer from respiratory muscle paralysis and dependence on chronic mechanical ventilation. In selected patients, diaphragm pacing (DP) through electrical stimulation of the phrenic nerves provides an alternative to mechanical ventilation with significant advantages in life quality.Methods: A case report of an individual who successfully underwent DP using intramuscular diaphragm electrodes. A brief review of the state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 61 publications
(127 reference statements)
0
49
0
Order By: Relevance
“…71 Early implantation, even within weeks of acute SCI, of all system components is ultimately envisioned. 71 DiMarco et al 73 have recently described in detail shortcomings of currently used EPR systems and outlined needs for their further development. In most cases, viability of only one phrenic nerve is not sufficient to allow breathing exclusively by EPR only.…”
Section: 68mentioning
confidence: 99%
See 2 more Smart Citations
“…71 Early implantation, even within weeks of acute SCI, of all system components is ultimately envisioned. 71 DiMarco et al 73 have recently described in detail shortcomings of currently used EPR systems and outlined needs for their further development. In most cases, viability of only one phrenic nerve is not sufficient to allow breathing exclusively by EPR only.…”
Section: 68mentioning
confidence: 99%
“…In recent years, it has been shown that accurate mapping of the phrenic nerve motor points permits successful laparoscopic implantation of intramuscular electrodes within the costal portion of each hemi-diaphragm. 51,73,71,72 Such procedure involves placement of four laparoscopic ports to the abdominal cavity for creation of a pneumoperitoeum, visualization of the diaphragm, diaphragmatic mapping by electrical stimulation and implantation of two electrodes at the motor points in each hemi-diaphragm. 73 The electrode wires are tunneled subcutaneously to the chest wall where they exit and connect to an external stimulator.…”
Section: 68mentioning
confidence: 99%
See 1 more Smart Citation
“…Accessory muscles can also assist the diaphragm by lifting the upper thorax. Abdominal muscles are the primary muscles for cough and include the rectus and transversus abdominis and the internal and external obliques [1][2]. Patients with upper-cervical spinal cord injury (SCI) have paralysis of these respiratory muscles (although accessory respiratory muscles may still be active).…”
Section: Introductionmentioning
confidence: 99%
“…Between 200 and 400 new SCI patients each year in the United States have this paralysis and the associated respiratory failure. Atelectasis and infection are the number one cause of death for these individuals [1][2].…”
Section: Introductionmentioning
confidence: 99%